Precarious mobility: experiences of platform delivery people for the GAM of Costa Rica - Jiménez-Barboza, Gustavo Adolfo (2024)
The article, from an urban sociology perspective, explores the precarious mobility experienced by platform workers in the Greater Metropolitan Area (GAM) of Costa Rica. The interactions of these people with the bicycle as a means of transport, its impact on sustainability and resilience, as well as the implications for their body, health and mobility were investigated. Their experience of the city, the relationship with platform companies and other key players, such as clients and co-workers were also analyzed. The theory selected to study the mobility dynamics and experience was motility, since it focuses on understanding how people gain or lose mobility capital through their disputed capitals in the city. The aim of this analysis is to comprehend the geographic and social dynamics that surround these workers, and to promote critical reflection on their displacement, work and life conditions. The methodology used for this research is qualitative, based on exploration and ethnographic interviews, as well as semi-structured interviews with delivery people.